Resilient integrated farming system models in irrigated agriculture - C, Jayanthi; C, Vennila; V, Varshini S (Indian Farming, 2021)
The farm diversifications with crops and livestock components were found to have synergies in the system in term of productivity, profitability and sustainability. The integration is source for providing food and nutritional security of the ever increasing population. Adopting suitable interventions, for example introduction of fodder component in the system increases forage availability, leads to improved productivity of animals within the system. Further, the direct and indirect effect of fertilization for enhancing productivity provides clearly the synergistic dimension of crop livestock integration. The targeted feeding intervention of soil and livestock component increases energy production, gross income and soil fertility improvement. The location specific strategic adoptive agronomic interventions employed in crop livestock integration helps in strengthening physical, chemical and biological environment. Adoption of farming system could able to endure shocks or stress due to biotic and abiotic factors through various interventions.Thus, IFS attempts to formulate proxies of resilience that characterise towards stress or to respond to favourable conditions.